Encapsulation of lutein into swelled cornstarch granules: Structure, stability and in vitro digestion. (1st December 2018) - Li, Songnan; Wang, Chan; Fu, Xiong; Li, Chao; He, Xiaowei; Zhang, Bin; Huang, Qiang
Highlights: Cornstarch-lutein composites were prepared at different temperature. Mechanism for cornstarch-lutein composite formation was investigated. Cornstarch-lutein composites exhibited enhanced lutein storage stability. Lutein in the composites can effectively release under simulated intestinal condition. Abstract: Swelled cornstarch granules incubated at different incubation temperatures was prepared as a complexation matrix to encapsulate lutein. Increasing incubation temperature (55–70 °C) induced the gelatinization of cornstarch, resulting in enhancement of swelling power (1.67–6.26 g/g) and lutein content (0.78–4.86 mg/g). A decreased (double helix of amylopectin) and an increased (single helix of V-amylose) enthalpy change were associated with the increased incubation temperature. The retention index of lutein in the composites incubated at 65 °C and 70 °C could achieve 76% after 21 days of storage. Less than 30% of lutein in the composites was released after incubating for 120 min under stomach conditions. Fast lutein release was observed during the first 20 min intestinal digestion, consistent with starch hydrolysis data. This study opens a promising pathway for swelled cornstarch granules as delivery carriers of bioactive ingredients, which are of vital importance for their potential use in the sensitive food supplement.